Dynamics of the edge of a topological quantum fluid with and without emergent conformal symmetry - Tan, Fei (Nanyang Technological University, 2024)
The fractional quantum Hall (FQH) effect has become one of the most studied phenomena in condensed matter physics for the past 40 years. One classic approach studying these systems is to compute their thermal Hall conductance (THC) since it can be a quantized quantity for certain FQH states and they do not depend on the details of the system. The quantized value of THC, which is an integer or fractional value in units of $κ_0$ ($κ_0 = π^2 k_B^2/(3h)$), can be used to determine the non-Abelian nature of FQH states. This quantization however can only be robust if the edge of the system is modelled by using the chiral Luttinger liquid ($χ$LL) under the linear dispersion. In experiments, this model may break down due to the nonlinearity of the confinement potential and the finite temperature effect.